Characterization of luminescent dosimeters for sterile insect technique - ARICIA RAVANE PEREIRA DA CRUZ; Lucas Mateus Ferreira de Amorim; Alcilene Cristina da Silva; Viviane Khoury Asfora; Vinicius Saito Monteiro de Barros; Aline Taiane Macedo Pinto; Charles Nilton do Prado Oliveira; Jair Fernandes Virginio; Helen Jamil Khoury (Brazilian Journal of Radiation Sciences)
The Sterile Insect Technique, or SIT, is an environment-friendly insect pest control method and uses gamma rays or X-rays to sterilize insects, remaining sexually competitive but cannot produce offspring. The dose control during the SIT procedures is essential for the quality of the irradiated product or material.  Insects that receive too low a dose are not sufficiently sterile and those that receive too high a dose may be uncompetitive. There are few dosimetric systems used for the dose control during the irradiation procedure. The aim of this paper is to characterize the Optically Stimulated (OSL) response of Li2B4O7:Cu,Ag, synthesized by the Nuclear Energy Department of the Federal University of Pernambuco and the MTS-N dosimeters to be used for SIT dosimetry and applied in Moscamed Brazil’s pest and vector control programs. The results were evaluated using the student’s t-test. Applying the hypothesis that the results obtained with the three types of dosimeters are similar, the test showed that with 99% confidentiality the hypothesis is accepted, that is, the results of the three types of dosimeters are similar. It is possible to conclude that the OSL Li2B4O7:Cu,Ag, and the TL MTS-N can be used for dose control during the SIT irradiation procedures.